2008
DOI: 10.1111/j.1651-2227.2008.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical closure of the patent ductus arteriosus and its effect on the cerebral tissue oxygenation

Abstract: The ductal clipping in se has no negative effect on the cerebral oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…During this early period, most ELBW infants have large PDA with massive shunt flow (left to right, right to left, or bidirectional). For example, LVCO in infants with significant LR shunt through large PDA may double compared with those without PDA, which influence CBF because of a stealing shunt flow from the descending aorta to the main pulmonary artery (35,36). However, the direction and the amount of the shunt flow often do not depend on the BP but on the pulmonary vascular resistance, which in turn, depends on the respiratory status.…”
Section: Discussionmentioning
confidence: 99%
“…During this early period, most ELBW infants have large PDA with massive shunt flow (left to right, right to left, or bidirectional). For example, LVCO in infants with significant LR shunt through large PDA may double compared with those without PDA, which influence CBF because of a stealing shunt flow from the descending aorta to the main pulmonary artery (35,36). However, the direction and the amount of the shunt flow often do not depend on the BP but on the pulmonary vascular resistance, which in turn, depends on the respiratory status.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that changes in DA flow may influence regional cerebral oxygen saturation very quickly. Vanderhaegen et al [20] found that 5 min after surgical closure of the PDA there was an increase of cerebral rSO 2 , which then disappeared by 20 min after clipping.…”
Section: Discussionmentioning
confidence: 99%
“…However, slower infusion rates did not have such an impact on brain haemodynamics [61]. Surgical closure of the PDA showed no consistent effects on cerebral circulation and oxygenation [53,54,55,56]. …”
Section: Interventions That Affect Oxygen Delivery To the Brainmentioning
confidence: 99%
“…The effect of a haemodynamically significant PDA or its treatment on cerebral haemodynamics and oxygenation is addressed in a number of studies using NIRS and other monitoring methods [46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61]. PDA may be a determinant in blood flow redistribution causing decreased blood pressure and rSt O 2 and increased FOE [57].…”
Section: Interventions That Affect Oxygen Delivery To the Brainmentioning
confidence: 99%